Exploring the Economic Recovery of Italy’s Regions Post-COVID-19: A focus on Energy, Services, ICT Opportunities, and the Digital Divide - Marino, Alfonso; Pariso, Paolo; Picariello, Michele (International Journal of Energy Economics and Policy, 2023)
The World is gradually coming out of the COVID-19 emergency and what emerges from the Italian scenario presents two sides of the same coin. A large part of the investments made at this juncture have been distributed directly to the regions. Unfortunately, in the last nine years, the twenty Italian regions have adopted different ITCs and distributed different levels of services and wealth. In doing so, there has been a lack of opportunity and development. The paper aims to understand how the Italian regions have recovered economically by analyzing variables such as services, the digital divide, energy management and the economic inequality. The investigation with a qualitative and quantitative analysis helps to understand these issues for Italian and non-governmental institutions.